VARIATIONS IN OCEANOGRAPHIC FACTORS AND THEIR POSSIBLE RELATION TO FLUCTUATIONS IN OIL SARDINE AND MACKEREL CATCHES OFF MANGALORE COAST - Suresh, K; Reddy, M P M (Indian Journal of Fisheries, 2011)
Among the important oceanographic parameters considered, the effect of sea water tensperature and salinity on the Evaitebility of oil sardine and mackerel appear to be very significant. The best catches of oil sardine were obtained when surface-water temperature ranged from 27.7Â°C and 29.9’’C and surfjce salinity â€¢ ranged between 32.6 %. and .34.9 %.. No definite relat’oaship was found between phytoplaaikton and oil sardine. High aibundance of mackerel was recorded when the r:nge in surface-water temperature and surface salinity was from 28.4 to 29.9Â°C and 32.6 to 34.9 %. respectively. Correlation betw-sen zooplanktoa and mackerel has not revealed any exact relationship between the two.